Direct Aromatic CH Trifluoromethylation via an Electron‐Donor–Acceptor Complex. Issue 23 (23rd April 2015) - Cheng, Yuanzheng; Yuan, Xiangai; Ma, Jing; Yu, Shouyun
Abstract A novel electron‐donor–acceptor (EDA) complex‐mediated direct CH trifluoromethylation of arenes with Umemoto's reagent has been developed. This transformation has been enabled by an unprecedented EDA complex formed by Umemoto's reagent and an amine, which was supported by experiments and theoretical calculations. The radical‐based methodology presented here allows to access highly‐functionalized trifluoromethyl arenes in up to 81 % chemical yield.